Bacterial pathogens in wound infection and their antimicrobial susceptibility pattern in a medical college hospital, in Dhaka, Bangladesh - Afroz, Sadia; Sarkar, Dipika; Khatun, Khadeza; Khan, Tarek Mahbub; Paul, Shikha (International Journal of Research in Medical Sciences, 2020)
Background: Wound infection is a major health problem that results in prolong hospital stay, increased treatment cost and are responsible for significant mortality and morbidity worldwide. The aim of the present study was to isolate and identify the bacterial pathogens causing wound infection and to determine their antimicrobial susceptibility profile. Methods: This cross sectional study was conducted at the Department of Microbiology, Sir Salimullah Medical College, Dhaka from January 2016 to December 2016. Wound swab samples were collected and inoculated into appropriate media. The bacterial pathogens were identified by using standard microbiological methods. Antimicrobial susceptibility test were performed using disc diffusion technique following Kirby-Bauer method. Results: Out of 239 wound swab samples analyzed 173 (72.4%) were culture positive. Majority (35.3%) of culture positive cases were in age group 16-30 years and 60.1% were male. Staphylococcus aureus (36.9%) was the predominant isolate, followed by Escherichia coli (35.8%), Pseudomonas spp. (17.3%) and Proteus spp. (5.8%). Bacterial isolates were highly resistant Amoxicillin (89-100%), Cephalosporin (60-100%), Ciprofloxacin (53-71%), while they were least resistant to Imipenem (0-14%) and Amikacin (17-30%). Conclusions: In the present study most of the isolates showed high rate of resistance to commonly used antibiotics. Therefore regular monitoring and rational use of antibiotic should be practiced.